World Oil Crisis and its Impacts on the Petroleum Market and the Economy of Vietnam - Bui, Xuan Hoi (International Journal of Energy Economics and Policy, 2021)
On April 21st 2020, for the first time in the word's history, the price of oil contracts for May delivery in the US dropped sharply to below 0 USD and stopped at a negative price as of 37.63 USD/barrel. The world oil market really fell into crisis, which had a significant impact on the oil industry of Vietnam. This article focuses on analyzing and clarifying the essence of “negative oil price” as well as the world oil market crisis and its impacts on the petroleum market in Vietnam. The findings indicate that the negative oil price was simply the result of a trading session in futures market, but its nature was the interaction between oil futures market and the physical market characterized by the disequilibrium in short-term. A scenario of low oil price dynamics is analyzed and predicted for the coming time. Thereby, the paper provides recommendations to the oil industry and macro governance of Vietnam in order to appropriate countermeasures in this difficult period. Keyword: Oil price, international oil market dynamics, Vietnam's oil industry and Economy JEL Classifications: D4, Q31, Q41, Q43. Q48 DOI: https://doi.org/10.32479/ijeep.10720